Finance at the crossroads: Geographies of the financial crisis and its implications. - Wójcik, D (Pion Ltd., 2011)
The financial crisis that started in 2007 is by no means a closed chapter of modern history. New foreclosures in the USA abound, economic recovery around the world seems fragile, and regulatory reform is only gaining traction. Finance is still very much at the crossroads. The task of diagnosing the crisis is far from complete, not to mention the task of generating ideas about the future structure and role of finance in economy and society. Geographical perspectives should play a part in this debate. The battle of interpretations of the crisis continues.